MEDIASI INDIA DALAM PERPINDAHAN DAN PENYEBARAN KULTUR DAN PERADABAN PERSIA: Islamisasi di Asia Tenggara - Mohammad Ali Rabbani (Media Syari'ah, 2017)
An effective and constructive role played by the Indian Muslims in the dissemination of Persian culture and civilization in Southeast Asia is quite important. Role of Indian Muslims is expansion one of the three theories about the origin of the arrival of Islam in Southeast Asia, i.e. the theory of Arabic, Indian and Eastern (Persian and Chinese). Historical Indications and documentary about the background of India’s important role to the presence of the Iranian people in Southeast Asia appeared through the presence of Iranian families descent who settled in major cities, as well as historic religious buildings and old tombs associated with the Iranian people. Iran names that exist in the old cemetery headstone of Iranian people with Persian language and religious tradition associated with Muharram and also usage of the name and title of Shiite at mosques and religious centers are witness documentary from Iran-India cultural assimilation that has moved into the region. Although the cultural traditions of India have friction and changes due to ethnic assimilation of Iranian descent who lived with the tribe and Banggali Indian descent, but the generation that remains in Southeast Asia still proud of their Iranian aspect. Despite pressure from the colonial party, the Communist government and military hegemony in the region, they were still able to play a major role in the defense of Islam and Islamic culture and aspects of Iranian in Southeast Asia.